2022
DOI: 10.3390/cryst12081114
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation to Confirm the Presence of TiB2 Reinforcements in the Matrix and Effect of Artificial Aging on Hardness and Tensile Properties of Stir-Cast LM4-TiB2 Composite

Abstract: The present work focuses on the effect of multistage solution heat treatment (MSHT) and artificial aging on two-stage stir-cast LM4 + TiB2 (1, 2, and 3 wt.%) composites on the mechanical properties as compared to as-cast and single-stage solution heat-treated (SSHT) composites. Two novel tests, viz. the confirmation hardness test and the chemical analysis test, were performed to ensure the soundness of the casting and uniform distribution of TiB2 within the matrix. Samples subjected to MSHT + aging at 100–200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…From the microstructures, it can be confirmed that there is no slag nor porosity, which indicates the soundness of the two-stage stir casting method. Formation of metastable intermetallic phases (Al 2 Cu, Q, and Mg 2 Si) is validated by XRD analysis from prior research [26,27,36], which are also in line with the literature.…”
Section: Optical Microstructure Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…From the microstructures, it can be confirmed that there is no slag nor porosity, which indicates the soundness of the two-stage stir casting method. Formation of metastable intermetallic phases (Al 2 Cu, Q, and Mg 2 Si) is validated by XRD analysis from prior research [26,27,36], which are also in line with the literature.…”
Section: Optical Microstructure Analysissupporting
confidence: 80%
“…Both reinforcements were bought from NANOCHEMAZONE INC, Canada. They have an average particle size of (TiB 2 -6.765 µm and Si 3 N 4 -26 µm), which was determined using a scanning electron microscope (SEM) [26,27]. Both TiB 2 and Si 3 N 4 are hard reinforcement particles with a hardness value of 2468 and 1750 VHN [28]; the unique properties of these hard reinforcement particles help in attaining enhanced properties of the cast composites when added separately to the LM4 matrix.…”
Section: Phase Imentioning
confidence: 99%
“…The agglomeration problem associated with CNTs inclusion is avoided by selecting proper casting parameters. Uniformity in reinforcement distribution is seen in the base matrix; with higher loadings of TiB 2 , higher grey particles are visible [35]. 15% reinforcement of TiB 2 leads to agglomeration due to faster solidification related to the reinforcements and matrix thermal expansion coefficients [36].…”
Section: Resultsmentioning
confidence: 97%
“…The melt temperature is got down to a 600 °C (semi-solid) state, and stirring continues until slurry formation occurs. Then preheated reinforcements are added to the molten melt [22,23] and stirred for about 10 min at 200 rpm, then the melt temperature is got upto to 745 °C and stirred again at 400 rpm for 10 min. Then after the molten composite mixture is poured into preheated (500 °C for 1 h) molds and left for solidification [24].…”
Section: Steps A-dmentioning
confidence: 99%